МАКТАБГАЧА ЁШДАГИ БОЛАЛАР ТАРБИЯСИДА АЛИШЕР НАВОИЙНИНГ АХЛОҚИЙ ҚАРАШЛАРИНИНГ АҲАМИЯТИ - Норбошева, М.; Исмоилова, И. (SCIENCE and SOCIETY, 2019)
The article is devoted to the description of ideas of the great thinker Alisher Navoi on morality and the role of his heritage in the education and formation of the children of pre-school age and personality in whole.
Keywords: Alisher Navoi; education; a child; spirituality; preschool age; great thinkers; behavior